EFEKTIVITAS EDUKASI PENERAPAN PHBS MELALUI PROGRAM SING PENTING BERAKZI DI DESA GLAGAHWERO - Auladani Sausan Amrulloh; Risa Wulandari; Iken Nafikadini; Globila Nurika (saintifika, 2022)
Glagahwero Village, Kalisat District, Jember Regency is an area that still has a high stunting rate. The prevalence of stunting in Kalisat ranks second highest in Jember Regency at 85.7%. Therefore, it is necessary to have the SING IMPORTANT BERAKZI program (Synergiscity of Stunting Prevention Efforts through Community Empowerment and Nutrition Intervention) in Glagahwero Village in which there is education on the application of PHBS (Clean and Healthy Behavior). The results of the situation analysis conducted using the interview method found that the majority of residents already have their own latrines at their homes, but they still defecate in the open, namely in the river. Apart from that, handwashing with soap (handwashing with soap) is also rarely practiced. This study aims to analyze the educational effectiveness of implementing PHBS (Clean and Healthy Behavior) which is one of the factors causing stunting. The research was carried out targeting elementary school children and mothers. The results showed that there was an increase between the pre-test and post-test. This proves that education on the implementation of PHBS is effective in preventing stunting in Glagahwero Village, Kalisat.